Drivers and outcomes of eco-design initiatives: a cross-country study of Malaysia and Australia - Iranmanesh, Mohammad; Fayezi, Sajad; Zailani, Suhaiza; Hyun, Sunghyup Sean (Springer Verlag (Germany), 2019)
In this study, we have developed and empirically tested a model of the antecedents of eco-design initiatives and their outcome using data that was collected from 255 environmental management representatives of certified manufacturing firms in Malaysia and Australia. Our model incorporates regulations, customer pressure, social responsibility, and expected business benefits as the antecedents to the eco-design initiatives, and investigates their environmental, economic, and intangible outcomes. The results indicate that regulation and social responsibility are positively associated with eco-design initiatives, which have a positive effect on the environmental, economic, and intangible outcomes of firms in both countries. Only in Australia, customer pressure is the motivator of eco-design initiatives. As for Malaysia, expected business benefit is the driver of eco-design initiatives. This study extends the knowledge on the drivers and outcomes of eco-design initiatives in the upper middle and high-income countries. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.